Dao Companion to Neo-Confucian Philosophy - Makeham, John.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This Companion is the first volume to provide a comprehensive introduction, in accessible English, to the Neo-Confucian philosophical thought of representative Chinese thinkers from the eleventh to the eighteenth centuries. It brings together nineteen essays on a range of topics in Neo-Confucian philosophy, embracing natural and speculative philosophy through to virtue ethics and political philosophy. Written for undergraduate and postgraduate university students in philosophy and Chinese history courses, as well as academics, the Companion is distinguished by several features: It demonstrates the key role played by philosophical discourse in Neo-Confucian self-cultivation; it evidences the fundamental connections that were posited between morality in human society and its cosmological and ontological underpinnings; and it provides detailed insights into changing perspectives on key philosophical concepts and their relationship with one another.
Zhou Dunyi s Philosophy of the Supreme Polarity -- Shao Yong s Numerological-Cosmological System -- Zhang Zai s Theory of Vital Energy -- Cheng Yi s Moral Philosophy -- The Thesis of Single-Rootedness in the Thought of Cheng Hao -- Hu Hong s Philosophy -- Zhang Shi s Philosophical Perspectives on Human Nature, Heart/Mind, Humaneness, and the Supreme Ultimate -- Zhu Xi s Cosmology -- Zhu Xi s Moral Psychology -- Lü Zuqian s Political Philosophy -- Neo-Confucian Philosophy and Genre: The Philosophical Writings of Chen Chun and Zhen Dexiu -- Lu Xiangshan s Ethical Philosophy -- The Four Masters of Mingzhou: Transmission and Innovation among the Disciples of Lu Jiuyuan (Xiangshan) -- Metaphysics and the Basis of Morality in the Philosophy of Wang Yangming -- Wang Yangming as a Virtue Ethicist -- Liu Zongzhou on Self-Cultivation -- Wang Fuzhi s Philosophy of Principle (Li) Inherent in Qi -- Li Guangdi and the Philosophy of Human Nature -- Dai Zhen on Human Nature and Moral Cultivation.
Keywords: Philosophy (General).; Philosophy, modern; Philosophy; Regional planning; Religion (General).; Philosophy; Non-Western Philosophy; Religious Studies; Philosophy of Religion; History of Philosophy; Regional and Cultural Studies